Process evaluation and in vitro selectivity analysis of aptamer-drug polymeric formulation for targeted pharmaceutical delivery - Tan, K.; Lau, John; Danquah, M. (2018)
Masson SAS Targeted drug delivery is a promising strategy to promote effective delivery of conventional and emerging pharmaceuticals. The emergence of aptamers as superior targeting ligands to direct active drug molecules specifically to desired malignant cells has created new opportunities to enhance disease therapies. The application of biodegradable polymers as delivery carriers to develop aptamer-navigated drug delivery system is a promising approach to effectively deliver desired drug dosages to target cells. This study reports the development of a layer-by-layer aptamer-mediated drug delivery system (DPAP) via a w/o/w double emulsion technique homogenized by ultrasonication or magnetic stirring. Experimental results showed no significant differences in the biophysical characteristics of DPAP nanoparticles generated using the two homogenization techniques. The DPAP formulation demonstrated a strong targeting performance and selectivity towards its target receptor molecules in the presence of non-targets. The DPAP formulation demonstrated a controlled and sustained drug release profile under the conditions of pH 7 and temperature 37 °C. Also, the drug release rate of DPAP formulation was successfully accelerated under an endosomal acidic condition of ~pH 5.5, indicating the potential to enhance drug delivery within the endosomal micro-environment. The findings from this work are useful to understanding polymer-aptamer-drug relationship and their impact on developing effective targeted delivery systems.